2015
DOI: 10.1016/j.schres.2014.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Losing the sugar coating: Potential impact of perineuronal net abnormalities on interneurons in schizophrenia

Abstract: Perineuronal nets (PNNs) were shown to be markedly altered in subjects with schizophrenia. In particular, decreases of PNNs have been detected in the amygdala, entorhinal cortex and prefrontal cortex. The formation of these specialized extracellular matrix (ECM) aggregates during postnatal development, their functions and association with distinct populations of GABAergic interneurons, bear great relevance to the pathophysiology of schizophrenia. PNNs gradually mature in an experience-dependent manner during l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 183 publications
5
119
1
4
Order By: Relevance
“…TH-positive fibres are considered to be a constitutive part of the interneuronal circuits within the frontal cortex. In previous studies, it was suggested that a deficit of interneurons in the frontal cortex; that is, a neuronal network deficit, might be one of the pathogenic mechanisms responsible for schizophrenia (19). In this study, we did not detect any gender-dependent differences in the density of TH-positive fibres in the frontal cortex, which disagrees with the findings of previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…TH-positive fibres are considered to be a constitutive part of the interneuronal circuits within the frontal cortex. In previous studies, it was suggested that a deficit of interneurons in the frontal cortex; that is, a neuronal network deficit, might be one of the pathogenic mechanisms responsible for schizophrenia (19). In this study, we did not detect any gender-dependent differences in the density of TH-positive fibres in the frontal cortex, which disagrees with the findings of previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Most cortical PV neurons, and a small number of PCs, are ensheathed by perineuronal nets (PNNs), a condensed form of extracellular matrix (Berretta et al, 2015) involved in the closure of developmental critical periods, regulation of synaptic plasticity, and are altered by oxidative stress (Cabungcal et al, 2013b;McRae and Porter, 2012). Several PNN proteoglycans, the lecticans, are highly glycosylated, and one, aggrecan, is highly enriched in mature PNNs (Bitanihirwe and Woo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They were initially described by Camillo Golgi using his Golgi technique (Golgi, 1893; Celio and Blümke, 1994; Celio et al, 1998). Investigations conducted in the last 25 years have shown that PNNs consist of a variety of glycoconjugates including hyaluronic acid, proteoglycans, and glycoproteins (Galtrey and Fawcett, 2007; Berretta et al, 2015; Smith et al, 2015). Recent studies have demonstrated that PNNs are formed during postnatal development and are critical for the regulation of a variety of synaptic functions including synaptic stabilization and synaptic plasticity (Galtrey and Fawcett, 2007; Berretta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations conducted in the last 25 years have shown that PNNs consist of a variety of glycoconjugates including hyaluronic acid, proteoglycans, and glycoproteins (Galtrey and Fawcett, 2007; Berretta et al, 2015; Smith et al, 2015). Recent studies have demonstrated that PNNs are formed during postnatal development and are critical for the regulation of a variety of synaptic functions including synaptic stabilization and synaptic plasticity (Galtrey and Fawcett, 2007; Berretta et al, 2015). The finding that PNNs and other components of the extracellular matrix are altered in several neurological and neuropsychiatric diseases suggests that a greater understanding of their structure and function could lead to novel therapies to treat these disorders (Viapiano and Matthews, 2006; Galtrey and Fawcett, 2007; Berretta et al, 2015; Maeda, 2015; Smith et al, 2015; Pantazopoulos and Berretta 2016; Sorg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%